Ethical Ideology and Ethical Judgments in the Portuguese Accounting Profession - Marques, Pedro Augusto; Azevedo-Pereira, José (2009)
The purpose of the present study is to examine the attitudes of Portuguese chartered accountants with respect to questions of ethical nature that can arise in their professional activity. Respondents were asked to respond to the Ethics Position Questionnaire developed by Forsyth (Journal of Personality and Social Psychology 39(1), 175–184, 1980), in order to determine their idealism and relativism levels. Subsequently, they answered questions about five scenarios related to accounting practices, with the objective of measuring their ethical judgments. Based on the idealism and relativism levels of our respondents, they were classified into one of four groups, representing different ethical ideologies (absolutism, exceptionism, subjectivism, and situationism). The results indicated that age was the major determinant of relativism. Contrary to previous research, older respondents revealed themselves significantly more relativistic than younger ones. Gender seems to be the most important determinant of ethical judgments; against expectations, men evidenced significantly stricter judgments than women in two of the five scenarios. Findings also indicated that respondents’ ethical judgments did not differ significantly based on their ethical ideology, supporting the idea that ethical ideology is not an important determinant of ethical judgments.
Keywords: Ethics; Ethical Judgment; Ethical Ideology; ethical decision-making; Business Ethics; Accounting